32. CLINICAL OUTCOMES AFTER ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION IN PATIENTS WITH A CONCOMITANT SEGOND FRACTURE (Vietnam Journal of Community Medicine, 2024)
Introduction: Segond fractures, characterized by avulsion injuries at the lateral tibial condyle's anterolateral structure (ALS) attachment, often coincide with anterior cruciate ligament (ACL) injuries, potentially leading to knee instability. This study aimed to determine if Segond fracture presence impacts ACL reconstruction outcomes.Materials and methods: this prospective study encompassed 14 patients (10 males, 4 females; mean age 31.9 years) who underwent ACL reconstruction, with a follow-up of at least one year.Results: at the final follow-up; Lysholm mean scores were 86,79 (from 79 to 96 points); mean VAS for knee pain was 1.4 (from 0 to 4 points); anterior tibial translation were 21.4% of patients; ROM in the knee joint was from mean 123.8º (from 110º to 138º) in flexon and mean 0.8º (from 0º to 3º) in extension; complications included 21.4% of cases with superficial wound infections and 14.3% of patients with grade I knee osteoarthritis.Conclusions: ACL rupture with Segond fracture results in satisfactory clinical outcomes with minimal complications.
Keywords: anterior cruciate ligament (ACL) reconstruction; anterolateral structure; Segond fracture